Physico-Chemical and Sensory Analysis of Instant Fufu Powder from Orange-Fleshed Sweet Potato and Cassava Starch Composite Extrudate Blends - Kolawole, Oladimeji Olubusayo; John, Nnenna Stella; Akolawole, Joseph Segun; Nduka, Emmanuel Orji; Orjiakor, Sylvester Nnaemeka; Obiegbuna, James Ejikeme; Odoh, Eunice Ngozi (Discoveries in Agriculture and Food Sciences, 2023)
Physico-chemical and sensory analysis of instant fufu powder from orange-fleshed sweet potato and cassava starch composite extrudates blends were carried out. Total number of six extruded fufu composite samples were generated and subjected to analysis using standard conventional methods. The result findings ranged as follows: 4.95 to 7.25, 3.75 to 5.40, 3.48 to 4.32, 0.83 to 2.14, 2.19 to 3.44 and 79.91 to 83.41% for moisture, protein, ash, fat, crude fibre and carbohydrates, respectively; 0.43 to 0.67 g/cm3, 2.43 to 3.61 g/mL, 3.06 to 8.78%, 6.93 to 14.65 g/100g, 14.57 to 20.06% and 1.00 to 5.00 min for bulk density, water absorption capacity, gelation, swelling index, solubility and wettability, respectively; 9.65 to 16.06 mg/100g, 7.04 to 10.52 mg/100g, 36.03 to 47.36 mg/100g, 55.31 to 63.47% and 4.76 to 8.65% for beta carotene, vitamin A, vitamin C, starch and sugar content, respectively. 263.50 to 1116.00, 251.50 to 632.50, 10.50 to 483.50, 424.50 to 966.50, 173.00 to 334.00 RVU, 4.87 to 6.96 min and 75.87 to 85.22oC for peak, trough, breakdown, final, setback viscosity, peak time and pasting temperature, respectively for the extruded composite flour blends. Sensory evaluation of the tepid water reconstituted fufu paste values ranged from 5.80 to 6.25, 5.75 to 6.40, 4.15 to 5.45, 4.30 to 5.75 and 5.10 to 5.70 for colour, flavor, handfeel, mouldability and overall acceptability, respectively.